Analisis Tingkat Kecemasan Satgas Siaga Covid-19 - Diana Tri Lestari; Efendi Efendi (Universitas Ngudi Waluyo, 2020)
The Covid-19 pandemic has a multi-sectoral impact in terms of health, education, social and economy as well as the emergence of social anxiety disorders in the community. The Covid-19 Task Force is a very high risk of exposure according to their duties and functions which must go directly to the community. This research aims to determine the level of anxiety of the Covid-19 task force. This research is a survey research with cross sectional research design. In this study, the sampling technique is total sampling with respondent criteria is active duty as a task force for at least 2 weeks and willing to be a respondent. Used 32 respondents. The instrument used in this study was the Covid-19 Anxiety Syndrome Scale (C-19ASS). The results of this study indicate that if there is a relationship between gender and the anxiety level of the covid-19 task force with P: 0.03, there is a relationship between the level of education and the anxiety level of the covid-19 task force P: 0.02. The recommendation of this research is that it can be used by the government in overcoming anxiety in society.AnxietyCovid 19 Task Force